PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, DAN PROFITABILITAS TERHADAP PENGHINDARAAN PAJAK PERUSAHAAN MANUFAKTUR PADA TAHUN 2018-2019 - Jennifer Priccila; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
Researchers aim to examine to determine the effect of company size, sales growth, and profitability on manufacturing company tax avoidance in 2018-2019. This type of research uses quantitative data with secondary data from financial and annual data from food and beverage manufacturing companies in 2018-2019. The research sample was obtained from 26 food and beverage manufacturing companies from 2018-2019, thus 19 research samples were obtained. The data analysis technique used statistical analysis and SPSS 25 software such as descriptive analysis, correlation coefficient, determination coefficient, significant F test and t-test, simple linear regression analysis, and classical assumption test. The results of this study indicate that there is a significant influence between company size, sales growth, and profitability on tax avoidance seen at the p-value <5% (Sig. 0,000).